Customers' needs and expectations on servicescape surveillance management. Issue 6 (10th October 2016) - Bonfanti, Angelo
Abstract : Purpose: The purpose of this paper is to identify customers' needs and expectations regarding servicescape surveillance management (SSM) in order to suggest to service managers how they can carefully design a service environment to ensure a high level of security while concurrently enhancing the customer service experience. Design/methodology/approach: Given that this study is explorative in nature, it is based on a specific method of qualitative data collection: focus group interviews. Three focus group sessions were organised with 24 Italian customers of retail stores, hotels and hospitals. The multi-expectation model proposed by Parasuraman, Berry and Zeithaml, which distinguishes between what customers consider acceptable (adequate service level) and what they hope to receive (desired service level), was chosen as the reference framework to investigate customers' needs and expectations from SSM. Findings: Servicescape surveillance must be compatible with customer satisfaction. Customers are acceptably satisfied when servicescape surveillance offers them feelings of physical safety, psychological security, economic security and the right to privacy. They desire that surveillance also allows them to live a positive service experience in sensorial, psychological, social and temporal terms. However, customers' expectations of adequate and desired service levels are different in terms of the presence, quantity and visibility of surveillance in the three service areas examined. Interestingly, customers expect to find more visible surveillance measures inside retail stores rather than in hotels and hospitals, but they prefer to receive invisible surveillance in the servicescape. Practical implications: Service managers should consider surveillance not as a cost or a tool for detecting and punishing inappropriate or criminal behaviour, but rather, as an opportunity for enhancing the customer service experience. They can invest in servicescape design elements, technological surveillance solutions and continuous training of security personnel to meet their customers' adequate and desired service levels. Originality/value: This study provides two major contributions. From the theoretical viewpoint, it extends knowledge of the hitherto under-researched area of SSM by identifying customers' needs and expectations of surveillance and the customer service experience, which are topics usually examined separately in the literature. In terms of managerial implications, it provides store/hotel/hospital managers with recommendations on how to design a servicescape that is both secure and pleasant.